2020
DOI: 10.1007/s40823-020-00056-7
|View full text |Cite
|
Sign up to set email alerts
|

Restoration at the landscape scale as a means of mitigation and adaptation to climate change

Abstract: Purpose of Review Although landscape-scale restoration efforts are gaining traction worldwide, their success is generally unknown. We review landscape-scale restorations to gain insight to whether focal ecological outcomes have been achieved, in the face of changing environmental conditions. Recent Findings Only 9% of the 477 articles that resulted from our search were studies of landscape-scale restorations. The majority (73%) of the landscape restorations from our study have occurred since the 1990s, indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 109 publications
1
18
0
1
Order By: Relevance
“…Landscape-scale restoration of natural systems (e.g. by increasing connectivity of geomorphological processes between different landscape units) benefits not only dynamic geomorphological interests but may alleviate biodiversity loss (von Holle et al 2020). While adaptation and intervention are most commonly expected to be in the nexus between geoheritage and ecosystem services, there may be other overlaps such as a geoheritage-based decision to allow bluffs on an eroding coastline to erode having an adverse effect on archaeological resources on the bluff tops (see Vousdoukas et al 2022 for a World-Heritage context).…”
Section: Ecosystem Services and Benefitsmentioning
confidence: 99%
“…Landscape-scale restoration of natural systems (e.g. by increasing connectivity of geomorphological processes between different landscape units) benefits not only dynamic geomorphological interests but may alleviate biodiversity loss (von Holle et al 2020). While adaptation and intervention are most commonly expected to be in the nexus between geoheritage and ecosystem services, there may be other overlaps such as a geoheritage-based decision to allow bluffs on an eroding coastline to erode having an adverse effect on archaeological resources on the bluff tops (see Vousdoukas et al 2022 for a World-Heritage context).…”
Section: Ecosystem Services and Benefitsmentioning
confidence: 99%
“…Hence, we devise five directions for future research. Given the overwhelming amount of TME studies on a patch and local scale identified here, research on large-scale restoration 186 will be needed to scale up mountain restoration to a landscape level. Geo-spatial technologies, such as remote sensing could aid with this, for instance through restoration potential and opportunity assessments for entire mountain ecosystems.…”
Section: Future Directions For Researchmentioning
confidence: 99%
“…Restoration needs a continued effort (in terms of time and economic and personal resources) of research and implementation. It is clear that research so far has been very productive, but the results obtained should be more effectively integrated with policy-making, general wetland restoration practices and with a landscape perspective [ 156 ], particularly under future climatic scenarios.…”
Section: Final Remarks and Conclusionmentioning
confidence: 99%